Perancangan Furnitur Berbahan Olahan Rotan Berbasis Smart Living Untuk Apartemen SOHO - Michael Pratama Kurniawan; Adi Santosa (Intra, 2016)
Limited land space in the urban areas drives citizens shifting into vertical housing solution, especially SOHO apartments. Advance technology development supports this new lifestyle trend by enables people work wherever and whenever desire without physical presents in the office. With this kind of lifestyle and way of working, the need of technology-based furniture is highly increasing or also called innovative furniture. The design of the furniture will be aimed for the American who are in the Gen Y generation group. Hence, the design would use rattan as the material, considering its environmentally friendly feature that is major influence on the target market’s decision on buying furniture. In the designing phase, the theories and literature are also reviewed, as well as experts, i.e. furniture business owners, are interviewed to get the design that answers the existing problems and the market needs.